(3GdTQM GdTGej dcJGH GdcGaj aj GdMSGHs - (3eMeO Hf Ydj Hf GdMSf Hf CMeO Hf Ydis; (3CHh aNQ GdOjf eMeO Hf GdMSf, GdMGSH GdcQNjs ((3eMeO Hf YHO GdbGgQ Hf gHI Gddg s)
(3ChdgG (B:s
(3GdMeO ddg NGdb GdNdb heHjf GdMb Cf GTQM dce cJGH GdcGaj hCHjf dce eG CZeVI ef cdeGJg hhQj Yfg aj daXGJg hCcTa Yf eTcdGJg s
(3BNQgG (B:s
(3heLehY Pdc NeSI hNeShf ceG NQL ChdkG s
(3HgG fXGe GdJYbjHIs
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI LjOI s
(3eUOQ GbJfGA GdCUd (B:s
(3GdSdjeGfjI (B- (3JQcjG (B(801) s
Keywords: (3GdQjGVjGJs